Great Speeches for Better Speaking : Listen and Learn from History's Most Memorable Speeches - Eidenmuller, Michael E. (London Mc Graw Hill, 2008)
Speeches given by Ronald Reagan, Edward Kennedy, Douglas MacArthur, John F. Kennedy, Barbara Jordan, and Mary Fisher guide the reader on how to perform powerful and inspirational acts of public speaking, and includes two CDs with the six example speeches.
Include Glossary and References
Keywords: Public speaking -- Speeches, addresses, etc